Rural entrepreneurship in place: an integrated framework - Muñoz, Pablo; Kimmitt, Jonathan (Entrepreneurship and regional development, 2019)
Agglomeration-oriented theories have grown significantly in the past decade in the explanation and promotion of entrepreneurship. Theoretical frameworks and normative models such as entrepreneurial ecosystems are insufficient to observe, explain, and inform policies at the communal level in rural contexts. In this paper, we propose a socio-spatial lens as a more fruitful way of understanding the holistic picture of rural entrepreneurship. By means of abductive research, we explore the distinct elements of entrepreneurial places in rural contexts and derive an integrated meso-level framework, comprising place-sensitive determinations and dimensions, to observe and further analyse the enabling conditions of such places. The findings obtained and the framework developed will be of great use for the evaluation and decision-making, regarding entrepreneurship in rural communities.